Advances in modeling semiconductor epitaxy: Contributions of growth orientation and surface reconstruction to InN metalorganic vapor phase epitaxy - Kusaba, Akira; Kangawa, Yoshihiro; Kempisty, Pawel; Shiraishi, Kenji; Kakimoto, Koichi; Koukitu, Akinori (Applied physics express, 2016)
We propose a newly improved thermodynamic analysis method that incorporates surface energies. The new theoretical approach enables us to investigate the effects of the growth orientation and surface reconstruction. The obtained knowledge would be indispensable for examining the preferred growth conditions in terms of the contribution of the surface state. We applied the theoretical approach to study the growth processes of InN(0001) and by metalorganic vapor phase epitaxy. Calculation results reproduced the difference in optimum growth temperature. That is, we successfully developed a new theoretical approach that can predict growth processes on various growth surfaces.